PERTUMBUHAN DAN PRODUKSI 2 VARIETAS KEDELAI HITAM (Glycine soja) TERHADAP PEMBERIAN BEBERAPA JENIS PUPUK ORGANIK (BOKASHI) DI LAHAN KERING - Muhammad Rizal; St Subaedah; Aminah Muchdar (Percetakan Umi Toaha Makassar, 2019)
This research aims, 1). To assess the growth and production of two black soybean varieties. 2). To examine the effect of using organic fertilizer on the growth and production of black soybean. 3). To examine the interaction between various types of organic fertilizers and varieties on the growth and production of black soybeans.This research was conducted at the practice site of the Gowa Agricultural Development Polytechnic (Polbangtan), located at Romanglompoa Village, Bontomarannu, Gowa District. This research was conducted from July to December 2018. Data obtained from observations were analysed statistically (Analysis of variance with the F test) in accordance with the design used. In this study the experiments were analysed using the Split Plot Design. If the variance shows that F count is real or very real, then the data analysis is continued with the test using the Least Significant Difference test (LSD). The results showed that Detam-3 varieties had a significantly different effect with Detam-4 on the growth and production of black soybean plants, mixed organic fertilizer (bokashi manure, rice straw, and rice husk) showed the best effect on the growth and production of black soybean, and there is no interaction between the type of organic fertilizer and soybean varieties on the growth and production of black soybean. It is recommended to use Detam-3 black soybean varieties accompanied by the use of bokashi organic fertilizer made from rice straw as part of a zero-waste farming system to support optimum production